Prior Knowledge Mapping on Natural Science - Permatadewi, Safira; Zen, Djunaidah Zen; Haryani, Maefa Eka (FMIPA UNNES, 2019)
This study aims to map the Prior Knowledge that is owned by prospective students of Natural Sciences TeacherTraining Faculty Unsri. The sample in this study were prospective science teachers who are students from theChemistry Education Study Program Unsri FKIP (n = 71). The instrument used in this study was a multiple choicequestion in the form of a three-tier test. Questions are developed based on learning objectives and the results of previousresearch studies on similar topics. The results of this study indicate that there is a tendency for FKIP Unsri IPAprospective students to still have misconceptions and high lack of knowledge. Questions that show a high misconceptionare found in the topic of menstruation and pregnancy. A high percentage of lack of knowledge is shown in the topic ofgametogenesis. While the highest understanding of concept can be seen in the topic of the reproductive organs. Thefindings of this study can be used as an illustration to determine the steps for planning learning activities so that theycan help minimize misconceptions that occur after the learning process takes place.